2021
DOI: 10.1101/2021.05.02.442364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basal forebrain cholinergic neurons are part of the threat memory engram

Abstract: Although the engagement of cholinergic signaling in threat memory is well established (Knox, 2016a), our finding that specific cholinergic neurons are requisite partners in a threat memory engram is likely to surprise many. Neurons of the basal forebrain nucleus basalis and substantia innonimata (NBM/SIp) comprise the major source of cholinergic input to the basolateral amygdala (BLA), whose activation are required for both the acquisition and retrieval of cued threat memory and innate threat response behavio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…While dopamine has also been proposed to encode salience across valence based on novelty induced dopamine release, we did not observe NE release to non-associated cues, suggesting a bias towards valence (Kutlu et al, 2021), we did not observe significant NE release to a novel, non-associated cue. Acetylcholine has been hypothesized to be a valence-free prediction error which responds to both positive and negative valence (Crouse et al, 2020;Hangya et al, 2015;Rajebhosale et al, 2021;Sturgill et al, 2020). It is likely that an interacting array of neuromodulators produces teaching signals necessary for prediction of incoming outcomes across valence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While dopamine has also been proposed to encode salience across valence based on novelty induced dopamine release, we did not observe NE release to non-associated cues, suggesting a bias towards valence (Kutlu et al, 2021), we did not observe significant NE release to a novel, non-associated cue. Acetylcholine has been hypothesized to be a valence-free prediction error which responds to both positive and negative valence (Crouse et al, 2020;Hangya et al, 2015;Rajebhosale et al, 2021;Sturgill et al, 2020). It is likely that an interacting array of neuromodulators produces teaching signals necessary for prediction of incoming outcomes across valence.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work has attempted to explain dopamine release dynamics by incorporating the effects of temporal uncertainty to explain dopamine release seen in multistage operant tasks. While dopamine and other neuromodulators are released in response to aversive as well as rewarding cues (Crouse et al, 2020;Hangya et al, 2015;Matsumoto & Hikosaka, 2009;Rajebhosale et al, 2021;Sturgill et al, 2020), the neuromodulatory basis of aversive prediction errors remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the point estimate of increased response to the CS- did not entirely explain the group difference in the acquisition of conditioned fear; some residual deficit may be attributable to a decreased response to the CS+ in the schizophrenia group. The response to the CS+ is thought to reflect cue-induced adaptive dopamine release 7 , similar to prediction error learning related dopamine release 45 . Studies using reinforcement learning paradigms have shown that while deficits in learning from rewards is associated with negative symptoms, learning from aversive outcomes may be spared in schizophrenia 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Those prior results are consistent with our current findings of relatively intact responses to the CS+ (a negative reinforcer). Finally, changes in other neurotransmitters, such as glutamate 42,43 , acetylcholine 44,45 and serotonin 46 , which play a role in fear conditioning, may also contribute to the impairments observed in schizophrenia in associative learning.…”
Section: Fear Conditioning In Schizophrenia Versus Anxiety Disordersmentioning
confidence: 99%
“…Behavioral and electrophysiology studies illustrate that the NBM-BLA circuit facilitates learning by controlling the consolidation of salient cues. For example, NBM cholinergic neurons fire rapidly in response to appetitive or aversive stimuli ( Zhang et al, 2004 ; Hangya et al, 2015 ; Rajebhosale et al, 2021 ) and cause transient and scaled increases in BLA acetylcholine levels ( Mark et al, 1996 ; Jing et al, 2020 ; Liu et al, 2021 ). Optogenetic stimulation of ChAT + terminal fields in the BLA enhances cue-reward learning ( Crouse et al, 2020 ) and prolongs fear extinction ( Jiang et al, 2016 ; Kellis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%